Risk preferences under heterogeneous environmental risk - Roland Olbrich; Martin F. Quaas; Andreas Haensler; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
We study risk preferences and their determinants for commercial cattle farmers in Namibia who are subject to high and heterogeneous precipitation risk, using data from questionnaire and field experiments, simulated data for on-farm precipitation risk and data on famers' previous place of residence. We find that the relationship between risk preferences and precipitation risk is contingent on early-life experience with this risk. We also find that adult farmers self-select themselves onto farms according to their risk preferences. Results are not confounded by background risks or liquidity constraint.
Keywords: D81; Q12; Q57; 330; risk preferences; environmental risk; experimental elicitation; endogenous preferences; self-selection; field experiment; Weidewirtschaft; Rinderhaltung; Landwirte; Risikopräferenz; Bodenbelastung; Namibia